Evidence of a link between resting energy expenditure and bone remodelling, glucose homeostasis and adipokine variations in adolescent girls with anorexia nervosa. Issue 1 (January 2016) - Maïmoun, L.; Guillaume, S.; Lefebvre, P.; Philibert, P.; Bertet, H.; Picot, M.-C.; Gaspari, L.; Paris, F.; Seneque, M.; Dupuys, A.-M.; Courtet, P.; Thomas, E.; et al.
Abstract Summary Low bone mass is a consequence of anorexia nervosa (AN). This study assessed the effects of energy deficiency on various bone and hormonal parameters. The interrelationships between energy deficiency and bone remodelling, glucose homeostasis and adipokines underscore the importance of preventing energy deficiency to limit demineralisation and hormonal alterations in AN patients. Introduction Low areal bone mineral density (aBMD) is a well-known consequence of AN. However, the impact of reduced energy expenditure on bone metabolism is unknown. This study assessed the effects of energy deficiency on bone remodelling and its potential interactions with glucose homeostasis and adipose tissue-derived hormones in AN, a clinical model for reduced energy expenditure. Methods Fifty women with AN and 50 age-matched controls (mean age 18.1 ± 2.7 and 18.0 ± 2.1 years, respectively) were enrolled. aBMD was determined with DXA. Resting energy expenditure (REEm ), a marker of energy status, was indirectly assessed by calorimetry. Bone turnover markers, undercarboxylated osteocalcin (ucOC), parameters of glucose homeostasis, adipokines and growth factors were concomitantly evaluated. Results AN patients presented low aBMD at all bone sites. REEm, bone formation markers, ucOC, glucose, insulin, HOMA-IR, leptin and IGF-1 were significantly reduced, whereas the bone resorption marker, leptin receptor (sOB-R) and adiponectin were elevated in AN compared with CON. In AN patients, REEm was positively correlated with weight, BMI, whole body (WB) fat mass, WB fat-free soft tissue, markers of bone formation, glucose, insulin, HOMA-IR, leptin and IGF-1 and negatively correlated with the bone resorption marker and sOB-R. Biological parameters, aBMD excepted, appeared more affected by the weight variation in the last 6 months than by the disease duration. Conclusions The strong interrelationships between REEm and bone remodelling, glucose homeostasis and adipokines underscore the importance of preventing energy deficiency to limit short- and long-term bone demineralisation and hormonal alterations in AN patients.